2017
DOI: 10.1088/1757-899x/271/1/012034
|View full text |Cite
|
Sign up to set email alerts
|

The management of building fire safety towards the sustainability of Malaysian public universities

Abstract: Abstract. Recently, there had been reduction in annual budgetary allocations to public universities in Malaysia due to some economic tensions. This situation had left many institutions in question with the options of scaling down their expenses as well as sourcing for other means of meeting up with the shortfalls in allocated funds. Hence, it affects the sustainability of the building itself. This paper is an attempt to look at the possibility of reducing incidents that could lead to expending unbudgeted fund … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 20 publications
0
11
0
1
Order By: Relevance
“…On the contrary, a well-designed building, not operated by an efficient firefighting team, is more prone to have fire safety issues. 24 As in the present case scenario, an active and alert firefighting team could douse a fire quickly, thereby preventing it from spreading to adjoining operating rooms and minimizing the loss of costly equipment.…”
Section: Figurementioning
confidence: 84%
“…On the contrary, a well-designed building, not operated by an efficient firefighting team, is more prone to have fire safety issues. 24 As in the present case scenario, an active and alert firefighting team could douse a fire quickly, thereby preventing it from spreading to adjoining operating rooms and minimizing the loss of costly equipment.…”
Section: Figurementioning
confidence: 84%
“…A review of the relevant literature (Meacham, 1999; Subramaniam, 2004; Cullen et al , 2015; Hassanain and Mudhei, 2006; Flynn, 2009; Marincioni and Fraboni, 2012; Nadzim and Taib, 2014; Campbell, 2017; Ebenehi et al , 2017) and applicable fire codes and standards (DSFRS, 2018; IBC, 2018; IFC, 2018; NFPA 10, 2018; NFPA 101, 2018; NFPA 80, 2019; NFPA 70, 2020) in the domain of fire prevention in educational facilities was carried out. This activity served to comprehend the various sources of fire hazards in educational facilities and the required prevention measures to eliminate their occurrence.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, students' behavior and response to fire emergency situations might be inefficient, due to lack of awareness about life safety measures (Subramaniam, 2004). Many educational facilities encounter poor obligation to fire safety prevention measures, which implies that they are designed and operated in a hazardous condition (Ebenehi et al , 2017; Marincioni and Fraboni, 2012). Thus, comprehensive fire safety assessments should be adequately and frequently performed in these facilities (Kodur et al , 2020; Meacham, 1999; Tillander, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Rahad(2015), revealed that, occupants of office buildings are usually exposed to psychological problems, such as fear of isolation in personalized space, causing loneliness that could lead to depression, stress, anxiety, and lowering interest in community affairs concerning fire risk inclusive. In a fire, disaster involving an office building (Ebenechi, 2017), the researchers highlighted that the fire risk to occupant's life is quite huge with respects to an office building, which are mostly low-rise buildings. This could be attributed to multiple floors in most of the buildings that generally created an increasing effect, requiring a more significant number of people traveling via vertical distances on the stair.…”
mentioning
confidence: 99%